Notes on the genus Astenus Dejean, 1833 in the Mediterranean and adjacent regions. A new species from Turkey, seven new synonyms, and additional records (Coleoptera: Staphylinidae: Paederinae) - Anlaş Si̇nan (Zootaxa, 2020)
Based on the study of types and additional material, new taxonomic and faunistic data on some species of the genus Astenus from the Mediterranean and adjacent regions are presented. Astenus henrii sp. n. from Turkey is described, illustrated, and distinguished from related congeners. The following new synonyms are proposed: Astenus procerus (Gravenhorst, 1806) = A. rufopacus Reitter, 1909 syn. n. = A. circumflexus circumflexus Jarrige, 1952 syn. n. = A. circumflexus scutellaris Coiffait, 1970 syn. n. = A. obliquus Jarrige, 1952 syn. n. = A. baali Coiffait, 1960 syn. n.; A. melanurus (Küster, 1853) = A. adonis Coiffait, 1960 syn. n.; A. thoracicus (Baudi di Selve, 1857) =A. jordanicus Coiffait, 1981 syn. n.